Evolution of the Arctic Calanus complex: an Arctic marine avocado? - Berge, Jørgen; Gabrielsen, Tove M; Moline, Mark A.; Renaud, Paul (Journal of Plankton Research, 2012)
Before man hunted the large baleen whales to near extinction by the end of the nineteenth century, Arctic ecosystems were strongly influenced by these large predators. Their main prey were zooplankton, among which the calanoid copepod species of the genus Calanus, long considered key elements of polar marine ecosystems, are particularly abundant. These herbivorous zooplankters display a range of adaptations to the highly seasonal environments of the polar oceans, most notably extensive energy reserves and seasonal migrations to deep waters where the non-feeding season is spent in diapause. Classical work in marine ecology has suggested that slow growth, long lifespan and large body size in zooplankton are specific adaptations to life in cold waters with short and unpredictable feeding seasons. Here, we challenge this understanding and, by using an analogy from the evolutionary and contemporary history of the avocado, argue that predation pressure by the now nearly extinct baleen whales was an important driving force in the evolution of life history diversity in the Arctic Calanus complex.